2020
DOI: 10.1080/15230406.2020.1794976
|View full text |Cite
|
Sign up to set email alerts
|

How do people perceive the disclosure risk of maps? Examining the perceived disclosure risk of maps and its implications for geoprivacy protection

Abstract: This research examines how people subjectively perceive the disclosure risk of a map using original data collected in an online survey with 856 participants. The results indicate that perceived disclosure risk increases as the amount of locational information displayed on a map increases. Compared to point-based maps, perceived disclosure risk is significantly lower for kernel density maps, convex hull maps, and standard deviational ellipse maps. The results also revealed that perceived disclosure risk is affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…That is particularly important for visualization of socially vulnerable people such COVID-19 patients. Kim et al [85] indicated that perceived disclosure risk increases as the amount of locational information displayed on a map increases, and it depends on factors as the map scale and the presence of information of other people. Compared to point-based maps, the perceived disclosure risk is significantly lower for kernel density maps, convex hull maps, and standard deviational ellipse maps.…”
Section: Discussionmentioning
confidence: 99%
“…That is particularly important for visualization of socially vulnerable people such COVID-19 patients. Kim et al [85] indicated that perceived disclosure risk increases as the amount of locational information displayed on a map increases, and it depends on factors as the map scale and the presence of information of other people. Compared to point-based maps, the perceived disclosure risk is significantly lower for kernel density maps, convex hull maps, and standard deviational ellipse maps.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming the point information into heat maps is another way to guarantee a good k-anonymity (Z. Wang et al, 2019), and heat maps are perceived as not disclosing privacy by map readers (Kim et al, 2021). Besides k-anonymity, the theoretical advantage of heat maps is the preservation of large clusters that are converted into hot spots in the heat map.…”
Section: Alternative Geomasking Methodsmentioning
confidence: 99%
“…And a recent study shows that visualisation with a high level of detail (e.g. with point symbols for addresses) are perceived as more risky for geoprivacy than heat maps for instance (Kim, Kwan, Levenstein, & Richardson, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, data sharing has become critical as research reproducibility has received growing attention in the scientific community (Alter & Gonzalez, 2018; Kedron, Li, Fotheringham, & Goodchild, 2021; McNutt, 2014). In the field of geographic information science (GIScience) and public health, however, sharing data can often lead to serious geoprivacy violation because data often contain people's confidential locational information, such as home locations and daily GPS trajectories (Haley et al., 2016; Kim & Kwan, 2021a; Kim, Kwan, Levenstein, & Richardson, 2021; Kounadi & Leitner, 2014; Kwan, Casas, & Schmitz, 2004; Richardson, Kwan, Alter, & McKendry, 2015). To protect people's geoprivacy when sharing data, researchers have developed and applied various geomasking techniques, which deliberately introduce spatial errors to location data to reduce disclosure risks (Armstrong, Rushton, & Zimmerman, 1999; Curtis, Mills, Agustin, & Cocknurn, 2011; Zandbergen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A greater distance between the original location and the geomasked location indicates a higher level of data confidentiality. Besides, spatial k‐anonymity is widely used to evaluate spatial data confidentiality and disclosure risk (e.g., Ghinita, Zhao, Papadias, & Kalnis, 2010; Kim et al., 2021; Wang & Kwan, 2020; Zhang et al., 2017). A spatial k‐anonymity index counts the number of all data locations within a buffer region centered at an original location having the distance between the original location and the geomasked location as the radius.…”
Section: Introductionmentioning
confidence: 99%